A Technique of NLAODV algorithm to get Routes of Nodes-List in Mobile Ad-hoc Network (MANET) - Naif, Saad Sulaiman; Idrees, Barzan Abdulazeez; Ibrahim, Ali Jalil; Majedkan, Naji A. (Science Journal of University of Zakho, 2022)
A Mobile Ad-hoc Network (MANET) is a group of nodes that connect to each other wirelessly without the use of a central server or a traditional network structure. In MANETs, data packets are sent through wireless channels to keep communication going. Ad-hoc On-Demand Distance Vector Routing is a MANET-related reactive routing technology that generates a path of nodes to a destination by broadcasting packets of route request across the network. In this kind of Routing protocol, a connection loss causes the source to send control (RREQ) on the network, causing network congestion and performance deterioration. This study offers a Node List (NLAODV) Node List Ad-hoc On-Demand Distance Vector routing method that includes links and path-nodes to identify if any node on the network is involved in the route discovery process for sending control packets from wireless source node to the wireless destination node. Simulation findings reveal that the proposed NLAODV algorithm minimizes flood Packets and get best network as it’s not necessary for all nodes to be present in route discovery.